Seedling morphology and development in the epiphytic cactus Epiphyllum phyllanthus (L.) Haw. (Cactaceae: Hylocereeae) - Almeida, Odair J. G. [UNESP]; Paoli, Adelita Aparecida Sartori [UNESP]; Souza, Luiz A.; Cota-Sánchez, J. Hugo (Torrey Botanical Society, 2013)
Seedling morphology is relevant in classification, taxonomy, and vegetation studies to understand plant life cycles, germination succession and requirements, and developmental progression. However, most morphological studies of seedlings lack analysis of organ anatomy, impeding the comprehension of series of development and establishment in a particular environment. Here, we have taken a traditional anatomical approach to examine the stages of seedling development in Epiphyllum phyllanthus, a holo-epiphytic cactus of tribe Hylocereeae. The goals were 1) to offer a comprehensive description of growth series in E. phyllanthus seedlings based on morphological and anatomical analysis and 2) to examine the initial growth phases in the life cycle of this species to identify organ development and understand their adaptive significance in relation to seedling establishment. Our results include descriptions of seed morphology, embryonic features, and seedling vascularization pattern in the root, hypocotyl, cotyledons, and epicotyl. The morphological and developmental patterns in E. phyllanthus seedlings have potential phylogenetic and ontogenetic implications in the Cactaceae. Characters such as the presence of mucilage on the seed coat, the lack of seed operculum, and large cotyledons in E. phyllanthus are comparable to basal cacti, but the root anatomy is more similar to columnar relatives. At the familial level, there is an apparent trend in decreasing number of phloem and xylem poles in the stele of primary root, correlated with degree of specialization and advanced phylogenetic position: tetrarch to septarch-octarch in basal lineages, tetrarch Cereus-type in columnar species, to the diarch vascular system in Rhipsalideae and some species with cylindric/globose stem. © Torrey Botanical Club.
Keywords: transition zone; anatomy; cactus; ecozone; epiphyte; life cycle; morphology; phylogenetics; phylogeny; seedling; seedling establishment; specialization; succession; taxonomy